Peripheral neuroblastic tumors with genotype–phenotype discordance: A report from the Children's Oncology Group and the International Neuroblastoma Pathology Committee123. Issue 3 (28th June 2012) - Suganuma, Rie; Wang, Larry L.; Sano, Hideki; Naranjo, Arlene; London, Wendy B.; Seeger, Robert C.; Hogarty, Michael D.; Gastier‐Foster, Julie M.; Look, A. Thomas; Park, Julie R.; Maris, John M.; Cohn, Susan L.; et al.
Abstract Background Of 4, 706 peripheral neuroblastic tumors (pNTs) registered on the Children's Cancer Group and Children's Oncology Group Neuroblastoma Study between 1989 and 2010, 51 cases (1.1%) had genotype–phenotype discordance characterized by MYCN amplification (indicating poor prognosis) and Favorable Histology (indicating better prognosis). Procedure To distinguish prognostic subgroups in the genotype–phenotype discordant pNTs, two subgroups, "conventional" and "bull's eye, " were identified based on the nuclear morphology. The "conventional" tumors (35 cases) included: Neuroblastoma, poorly differentiated subtype (NB‐PD, 26 cases) with "salt‐and‐pepper" nuclei; neuroblastoma, differentiating subtype (4 cases); ganglioneuroblastoma, intermixed (3 cases); and ganglioneuroma, maturing subtype (2 cases). The "bull's eye" tumors included NB‐PD with prominent nucleoli (16 cases). Clinicopathologic characteristics of these two subgroups were analyzed. N‐myc protein expression was tested immunohistochemically on available tumors. Results No significant difference was found between these two subgroups in the distribution of prognostic factors such as age at diagnosis, clinical stage, histopathology category/subtype, mitosis‐karyorrhexis index, ploidy, 1p LOH, and unbalanced 11q LOH. However, prognosis of the patients with "conventional" tumors (5‐year EFS 85.7 ± 12.2%; OS 89.3 ± 10.3%) was significantly better than those with "bull's eye" tumors (EFS 31.3 ± 13.0%; OS 42.9 ± 16.2%; P = 0.0010 and 0.0008, respectively). Immunohistochemically all (11/11) tested "conventional" tumors were negative, and 10/11 tested "bull's eye" tumors were positive for N‐myc protein expression. Conclusions Based on the presence or absence of prominent nucleoli (the putative site of RNA synthesis/accumulation leading to N‐myc protein expression), two prognostic subgroups, "conventional" with a better prognosis and "bull's eye" with a poor prognosis, were distinguished among the genotype–phenotype discordant pNTs. Pediatr Blood Cancer 2013; 60: 363–370. © 2012 Wiley Periodicals, Inc.